Synthesis of Schiff's Base Between Dialdehid Alginate and Chitosan and Testing of Antibacterial Properties - Kaban, Jamaran; Pasaribu, Seprinto (Journal of Chemical Natural Resources, 2023)
Schiff base synthesis has been carried out through a condensation reaction between dialdehyde alginate and chitosan. The first step is to oxidize Na-alginate using a sodium periodate (NaIO4) oxidizer, which produces alginate dialdehyde. The next step is FT-IR analysis, degree of oxidation, swelling ratio, and antibacterial properties. The FT-IR analysis results of alginate dialdehyde, which has been absorption peak at 1627.92 cm-1, show stretching group C=O and wave number 1026.13 cm-,1 stretching group COC (cyclic ether). The Schiff base has been absorption peak at 1635.64 cm-1, a stretching vibration group C=N. The degree of oxidation is 33%, and the swelling ratio is 50%. The testing of antibacterial which is conducted has been antimicrobials zone of Escherichia coli bacteria to Schiff base 0 mm and chitosan 0.225 mm; meanwhile, for Staphylococcus aureus bacteria antimicrobials zone which is Schiff base 1.916 mm and chitosan 0.333 mm. It can be concluded that Schiff base can inhibit the growth of Staphylococcus aureus bacteria than Escherichia coli bacteria were not inhibited.